Clinical Ethics Fellowship Programs in the U.S. and Canada: A Descriptive Study of Program Characteristics and Practices. - Fox, Ellen; Wasserman, Jason Adam (American Journal of Bioethics, 2025)
To address the current lack of knowledge about clinical ethics fellowship programs (CEFPs), we surveyed all 36 programs in the U.S. and Canada. The number of CEFPs has grown exponentially over the last 40 years and far exceeds previous estimates. Commonalities among CEFPs include: 88.8% require an advanced degree or rarely accept applicants without one; 91.7% of programs do not restrict applicants to a specific background such as medicine or philosophy; and 88.9% of programs compensate fellows. CEFPs vary widely on numbers of fellows trained in the last 3 years (1–111), numbers of consultations performed by each fellow (0–450), and salaries paid ($0-$95,000). Less than half of programs meet CEFP standards established by ABPD. Nonpaying programs and larger programs tend to have lower admission standards and lower expectations for fellows. We hope these data will help inform CEFP standards that promote quality and consistency without stifling desirable diversity and innovation.